Relationship between Organizational Intelligence and Innovations: Case of Lithuanian Sports Federations (Baltic Journal of Sport and Health Sciences, 2016)
Background.  Sports  organizations  exist  to  perform  tasks  that  can  only  be  executed  through  cooperative effort, and sports management is responsible for the performance and success of these organizations. The main problem concerning sports organizations and making them implement modern management paradigms is the duality of functions, which divides a sports organization into units increasing the internal competition and reducing the possibilities to create new knowledge. This undoubtedly affects the insufficiently productive functioning of a sports organization under modern conditions of globalization. Organizational intelligence (OI) could be a way to promote innovations, create and share knowledge (McMaster, 1998; Winand, Qualizza, Vos, Zintz, & Scheerder, 2013b).Methods.  Two  questionnaires  were  used  in  this  research:  first,  regarding  the  evaluation  of  organizational intelligence level, the second regarding the sports organization’s preparation for innovations.Results. One of the lowest evaluated OI factors was organizational openness and the highest rating was given to group work. Comparing OI internal dimensions score of sports organizations which implemented or not innovations during the last 12 months it became clear that there was a significant difference in the scores for organizational openness in sport organizations which implemented innovations and (M = 4.2747, SD = 0.82337) and for sport organizations which did not implement innovations (M = 3.5874, SD = 0.51288), p = .24 (two-tailed). Conclusion.  Sports  organizations  having  more  features  of  intelligent  organization  more  analyse  innovation development  opportunities  in  various  aspects,  but  the  level  of  intelligence  and  innovation  ideas  development has no relation, except for costs analysis. Sports organization becoming intelligent and developing innovations had advantage only in some phases of innovation development: situation analysis and decision making.Keywords:  sport federations, organizational culture, readiness to innovation process.